Determining the Carbon Footprint and Emission Hotspots for the Wine Produced in Cyprus - Litskas, Vassilis D.; Tzortzakis, Nikos G.; Stavrinides, Menelaos (My University, 2020)
International agreements and policies on climate change urge for a drastic reduction in greenhouse gas (GHG) emissions to prevent a temperature rise above 2 C at the end of the century. Determination of the product carbon footprint (CF), identifying carbon hotspots and examining ways for CF reduction is an essential step towards mitigation actions. Viticulture and winemaking are very important for the economy of Mediterranean regions, especially for the sustainability of rural areas. To determine the CF for wine, the Life Cycle Assessment (LCA) approach was adopted with system boundaries from vineyard to market. Input data were collected from 20 vineyards on the island of Cyprus, where the indigenous Xynisteri variety is cultivated and from an SME winery that uses the grapes to produce wine. The winery CF was 99,586 kg CO2-eq for 76,000 bottles produced (1.31 kg/0.75 L bottle). The uncertainty factor was determined to be 50%, which was considered adequate for the methodology followed. The share of electrical energy was 46%, of packaging 18% and of the vineyard 16%. Fuel (transportation and heating), as well as waste management (solid and wastewater) contributed 10% each to the CF. There is potential for mitigation of the CF by replacing the bottles currently used by lighter ones, lowering the energy use and reusing a part of the solid waste as fertilizer. Research towards eco-innovation of viticulture/winemaking is essential for reducing the footprint of the sector to promote sustainable wine production.
Keywords: Sustainable winemaking; LCA; Carbon balance; Greenhouse gases; Grapes